Geology Of Tanjung Medan ,Rokan IV Koto , Rokan Hulu District, Riau Province - Budi Prayitno; Susilo Susilo (Journal of Geoscience, Engineering, Environment, and Technology, 2018)
The Administrative of research area has been in Tanjung Medan, Rokan IV Koto, Rokan Hulu, Riau Province and geographically located at 0 ° 37 '28.488 "- 0 ° 40' 10.3692" LU and 100 ° 24 '55.6884 "- 100 ° 27 '37.5804 "BT. Research method used approach method and laboratory analysis to get data of geology modeling and re-construction of geological history in research area. Based on surface observation, the geology of research area consists of Slate (Permian-carbon), Granite intrusion (Permian-Trias) with distribution SouthWest-SouthEast on the center of map. Arenite Sandstone unit (Easly Eocene) unconformity with slate on the bottom. Alluvial Rokan river crosses all type off rocks from north to south of map. While structure growth in the research area have been joints structure with main stress Southwest-NorthEast, its similar with trend tectonic setting of Sumatra island, on the other hand reverse fault indicates the formation of a basin of extension stress in the early Eocene. the formation of basins in basement rocks begun at the time of the formation of the north-south trending northern form of the fault block forming horst and graben as well as accommodated the precipitation of pre-tertiary clastic materials. Whereas the Oligocene trans-tensional compression system accommodating the sedimentation system in the formed of arenite sandstone (SBPa) unconformity above the basement rocks simultaneously on the basin base decrease. The distribution of arenite sandstones based on the geological reconstruction covering all parts of the rock distribution which then undergoes the same weathering process of the formation of Bukit Barisan volcanic path that controls the development of geological structure up to the present.